A biologically active 53 kDa fragment of overproduced alanyl-tRNA synthetase from Thermus thermophilus HB8 specifically interacts with tRNA Ala acceptor helix. - Lechler, A (1997)
The alaS gene encoding the alanyl-tRNA synthetase (AlaRS) from Thermus thermophilus HB8 was cloned and sequenced. The gene comprises 2646 bp, corresponding to 882 amino acids, 45% of which are identical to the enzyme from Escherichia coli . The T. thermophilus AlaRS was overproduced in E.coli , purified and characterized. It has high thermal stability up to approximately 65 degrees C, with a temperature optimum of aminoacylation activity at approximately 60 degrees C, and will be valuable for crystallization. The purified enzyme appears as a dimer with a specific activity of 220 U/mg and k cat/ K M values of 118 000/s/M for alanine and 114 000/s/M for ATP. By genetic engineering a 53 kDa fragment of AlaRS comprising the N-terminal 470 amino acids (AlaN470) was also overproduced and purified. It is as stable as entire AlaRS and sufficient for specific aminoacylation of intact tRNAAla, as well as acceptor stem microhelices with a G3-U70, but not U3-A70, I3-U70 or C3-U70, base pair. The reduced binding strength of such microhelices to AlaN470 enabled, due to the resulting fast exchange of the microhelices between free and complexed states, preliminary NMR analyses of the binding mode and intermolecular recognition.